2022
DOI: 10.3390/ijerph19084822
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Tourists’ Preferences, Attitudes and Travel Expectations: A Study in Guayaquil, Ecuador

Abstract: Expectations about a destination influence the tourist experience during the travel process stages. In the post-COVID-19 normalcy, people are adjusting their priorities and social values. Therefore, it becomes crucial to identify tourists’ expectations before traveling. The objectives of this research were: (a) identify the preferences of tourists; (b) establish the attitudes of tourists; and (c) determine the expectations of tourists for post-COVID-19 destination selection. The study analyzed a sample of 491 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 50 publications
2
15
1
3
Order By: Relevance
“…By offering an emic perspective, the study highlights the transformation in tourists’ behaviour and psyche. The social factor reported in the study also echoes an emerging demand for urban tourism, also reported by Orden-Mejía et al (2022). Further, the current study brings rigour to the existing theoretical framework of perceived crowding and social motivation theory by exploring the post-pandemic tourists’ perceptions and motivations using a qualitative approach.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…By offering an emic perspective, the study highlights the transformation in tourists’ behaviour and psyche. The social factor reported in the study also echoes an emerging demand for urban tourism, also reported by Orden-Mejía et al (2022). Further, the current study brings rigour to the existing theoretical framework of perceived crowding and social motivation theory by exploring the post-pandemic tourists’ perceptions and motivations using a qualitative approach.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, McKercher (2021) also reported that people are unlikely to avoid travelling during a crisis where it is part of their lifestyle. The findings, especially price affordability, convenience and safety correlate with Orden-Mejía et al (2022) who examined the tourists’ preferences, attitudes and expectations in Guatemala City post-COVID-19. Understandably, the tourists’ psychological and behavioural patterns (in travel-decision-making), of developed and developing economies (both Shimla and Guatemala) differ, indicating a need for more studies in the latter.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Push factors such as relaxation, adventure and escape can explain the initial thrill, energising or “push” to travel and can steer tourists to certain places (Su et al , 2020). COVID-19 has altered travellers’ preferences, attitudes and expectations (Orden-Mejía et al , 2022) and has emphasised push factors (Çolakoğlu et al , 2021). Also, past literature has addressed the significant impact of push factors on perceived value (Dean and Suhartanto, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, due to the impact of COVID-19, the tourism industry is facing severe challenges such as prominent vulnerability and increased risk uncertainty [1][2][3]. Meanwhile, there are many supplies for tourism, and the potential tourism demand is still large [4][5][6].…”
Section: Introductionmentioning
confidence: 99%